Pembelajaran Kalender Islam Tematik untuk Anak Sekolah Dasar - Hamdani, Fahmi Fatwa Rosyadi Satria; Rojak, Encep Abdul (Program Pascasarjana Universitas Ibrahimy, 2017)
Calendar is one of the human's masterpiece in studying the regularity of the movement of celestial bodies such as the Sun, Earth and Moon. In Indonesia, generally found the Gregorian calendar that based on the movement of the sun and the Islamic calendar / Hijra with the motion of the Moon. Therefore, in an effort to introduce Islamic calendar to the society, researchers held a thematic learning about the Islamic calendar to children, in the activities of Ramadan Stars Camp (RSC) Imah Noong. The aim is to provide an introduction and understanding to the children about the Islamic calendar in the concept called â€œeduwisataâ€. This is done by the researchers so that children do not feel bored when presented materials related to the Islamic calendar. The method used in this research is descriptive analysis which researchers take the data in the form of a questionnaire to participants, then processed, classified, and conclusions. The results of this study are mostly children who participated in the RSC can find out about the history of Islamic calendar, the legal basis, the calculation system, and the names of the months in Islamic calendar system.